Dabigatran Therapy in Acute Ischemic Stroke Patients Without Atrial Fibrillation. Issue 9 (September 2015) - Kate, Mahesh; Gioia, Laura; Buck, Brian; Sivakumar, Leka; Jeerakathil, Thomas; Shuaib, Ashfaq; Butcher, Kenneth
Abstract : Background and Purpose—: Acute ischemic stroke patients are at risk of early recurrence. We tested the feasibility and safety of initiating dabigatran in patients, within 24 hours of minor stroke in patients without atrial fibrillation. Methods—: Minor stroke patients (National Institutes of Health Stroke Scale score ⩽3) without atrial fibrillation and evidence of acute infarction on magnetic resonance imaging were treated with dabigatran. Treatment began within 24 hours of onset and was continued for 30 days. The primary end point was symptomatic hemorrhagic transformation. Results—: A total of 53 patients with median (interquartile range) age of 68 (57–77) years and National Institutes of Health Stroke Scale score of 1 (0–2) were enrolled. Baseline diffusion-weighted imaging volume was 0.8 (0.3–2.4) mL. No patients experienced symptomatic hemorrhagic transformation. Three patients had evidence of asymptomatic petechial hemorrhagic transformation on day 7, which remained stable at day 30, while continuing dabigatran. Conclusions—: Dabigatran treatment within 24 hours of minor stroke is feasible. A larger randomized trial is required to confirm the safety and efficacy of this treatment approach. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT 01769703. Abstract : Supplemental Digital Content is available in the text.